Keefektifan Model Make A Match dalam Pembelajaran Matematika Siswa Kelas VI Sekolah Dasar di Kecamatan Marioriwawo - Kaharuddin, Andi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The purpose of this study was to determine the effectiveness of the model to Make a Match in mathematics learning 6th-grade students of Elementary School Marioriwawo Sub-District. This research is a quantitative experimental research. The population in the study were all 6th-grade students of Elementary School Marioriwawo Sub-District from 50 school. Determination of the sample was done by random sampling. Data analysis techniques used is descriptive statistics and inferential statistics using a single sample test. The results showed that the application of effective models in learning mathematics 6th-grade students of Elementary School Marioriwawo Sub-District in terms of the average learning outcomes 71.9, 80.4% activity and and the response to the application of the model 93.7%.